Classification Of Old Armenian Verb Structures In The Works Of Manuk Abeghyan - Dilbaryan , Narine (Bulletin of Yerevan University B: Philology, 2026)
Manuk Abeghyan’s linguistic research has always been based on the principle of diachronic description. Therefore, he began his study of the grammatical system of the Armenian language with Old Armenian, identifying the common features and systemic differences between Old Armenian and Modern Armenian, including grabar and ashkharabar. Of particular value is his study of the verb systems of Old Armenian and Modern Armenian, characterized by approaches that were innovative for their time. Manuk Abeghyan examined the characteristics of Old Armenian verbs, drawing on the rich linguistic material of classical manuscript sources from the 5th century, particularly the Bible, considered the "queen of translations" of Old Armenian. The renowned linguist provides a detailed description of the impersonal and personal forms of Old Armenian verbs. He reveals that the infinitive and past participle of Grabar often perform the role and function of conjugated verbs. They express predication, are distinguished by rich semantic diversity, become predicates, and their subjects are expressed in oblique cases; genitive, dative, or accusative. This is an important characteristic of the Old Armenian language. Abeghian made fundamental, still relevant, observations on the manifestations of verb aspect in Old Armenian and on the construction of intransitive passive structures. The famous linguist always supported his theoretical grammatical conclusions and classifications with numerous practical examples from ancient literary sources.